Assessment of Knowledge, Practices and Self-Reported Problems Related to Halitosis among the Students of Sharif Medical and Dental College and Bakhtawar Amin Medical and Dental College - Mahnoor Shahid, Wajih Malik, Marij Hameed, Usman Rashid, Sarmad Saif, Nauman Rauf Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Halitosis is the source of nuisance and can affect person’s own health. This can also create social issues and may decrease self-confidence. The main cause of large number of populations effected by this condition is lack of awareness, knowledge or non-accessibility to health care facility. Objectives: The aim of this study is to access the knowledge, practices and self-reported problems of halitosis among the students of Sharif Medical & Dental College, Sharif College of Engineering and Technology and Bakhtawar Amin Medical and Dental College Multan. Duration of Study: This cross-sectional study was conducted among students of Sharif Medical & Dental College Sharif College of Engineering and Technology and Bakhtawar Amin Medical and Dental College Multan from 1st July 2019 to 01st January 2022. Material and Methods: The data was collected using a questionnaire consisting of 13 questions includes three components i.e. knowledge, practices and self- reported problems. Practice and self -reported problems were assessed using special scoring system. Results: 500 students participated in the research program. Among all students, 69.8% had knowledge about halitosis. Responses to self-reported problems showed 7.2% of the participants suffered from halitosis. 29.8% and 30.4% reported dental caries and bleeding gums respectively. 25.6% mentioned about the dryness of mouth. 49.4% were concerned about social impact of their bad breath. Conclusion: Increasing awareness, knowledge about the cause and treatment options of this condition can improve the general health and well-being.